Pelaksanaan Corporate Social Responsibility - Luciani Amelia Hermawan; Iflah (Bandung Conference Series: Public Relations, 2023)
Abstract. Unilever's CSR (Corporate Social Responsibility) program continues from year to year with various themes and its own benefits for the community. The purpose of this observation was to find information and observe that the BKGN CSR program can be an activity that is beneficial and makes Pepsodent's products well-known to the public. This observation focuses on the company PT Unilever Indonesia which carries out CSR programs through its products. The research was conducted using a qualitative type method. PT Unilever Indonesia's CSR program carries the theme "Recovering Together with Indonesia's Healthy Smiles". BKGN (National Dental Health Month) is an activity carried out in various cities in Indonesia after the pandemic that hit Indonesia. The BKGN CSR program can describe an overview of the activities in the program. The results of this observation indicate that the existence of the BKGN CSR program is one of the attractions that has made Pepsodent's products increasingly known to the public. Abstrak. Program CSR (corporate social responsibility) Unilever terus berjalan dari tahun ke tahun dengan berbagai tema dan manfaat tersendiri bagi masyarakat. Tujuan observasi ini dilakukan adalah untuk mencari informasi dan mengamati bahwa program CSR BKGN dapat menjadi sebuah kegiatan yang bermanfaat serta membuat produk Pepsodent dikenal baik oleh masyarakat. Observasi ini berfokus pada perusahaan PT Unilever Indonesia yang melakukan program CSR melalui produknya. Penelitian dilakukan menggunakan metode jenis kualitatif. Program CSR yang dilakukan PT Unilever Indonesia mengangkat tema “Pulih Bersama dengan Senyum Sehat Indonesia”. BKGN (Bulan Kesehatan Gigi Nasional) adalah kegiatan yang dilakukan di berbagai kota di Indonesia setelah masa pandemi yang melanda Indonesia. Program CSR BKGN dapat mendeskripsikan gambaran mengenai kegiatan pada program. Hasil observasi ini menunjukan bahwa adanya program CSR BKGN menjadi salah satu daya tarik yang membuat produk Pepsodent semakin dikenal oleh masyarakat.